What Lies Behind Substantial Differences in COVID-19 Vaccination Rates Between EU Member States? - Franic, Josip (Frontiers in Public Health, 2022)
Background: Despite the billions of doses at disposal, less than three-quarters of EU citizens received a COVID-19 vaccine by the end of 2021. To explore why this is so, and in particular why transition societies experience stronger opposition to vaccination, this paper approaches the issue from the perspective of economic, political, and cultural challenges EU countries are facing at the moment. Methods: Data from Flash Eurobarometer 494 conducted in May 2021 were used to model the attitudes of EU citizens towards COVID-19 vaccination. Based on their views and intentions, respondents were divided into three categories: 1) already vaccinated/plan to get vaccinated; 2) indecisive; 3) refuse vaccination. Multilevel multinomial logistic regression was employed to understand what underlies the reasoning of each group. Results: The survey revealed that 13.4% of Europeans planned to delay vaccination against COVID-19, while 11.2% did not intend to get vaccinated. Although numerous demographic and socio-economic factors jointly shape their viewpoints, it is trust (in the authorities, science, peers, and online social networks above all) that strongly dominates citizens’ reasoning. Education also plays a pivotal role, which is reflected through an individual’s ability to critically assess information from various sources. Conclusion: The study results clearly illustrate how long-lasting structural problems can manifest in unforeseen circumstances if left unaddressed. It is hence of vital importance to learn the lesson and prevent similar issues in the future. This would require wide-ranging reforms aiming to repair the imperceptible psychological contract between citizens and the state authorities.